PEMODELAN DAN SIMULASI KANAL SATELIT TAK LINIER PITA TERBATAS UNTUK KOMMUNIKASI DIGITAL - Suwadi
Abstract : Digital satellite communication system has qualities, that is large covered area and has more quality than analog systems. Furthermore, because of power limitation of satellite system, so satellite\'s transponder operates in saturation to ensure maximum radiated power. At saturation, the transponder operates in nonlinear operating point that exhibiting both AM/AM and AM/PM conversions. Both of these nonlinear effects can lead to significant signal distortion and system performance impairment. The problems in satellite channel are transponder operates in saturation point and the channel operates on band-limited. In this research, modulation system using QPSK, characteristic of TWTA using Saleh\'s model and the overall satellite channel modeled as raised cosine filter and butterworth filter. In addition, on each path the signal is corrupted by Gaussian noise (AWGN). The purpose of this research, is system modeling, to create algorithm, to create software, simulation process and analysis. Signal on sub-channel is evaluated in time domain, eye-pattern, frequency domain, and signal constellation. Furthermore, this thesis investigates system performance based on average bit error probability versus arbitrary Eb/No using quasi-analytic simulation method. Based on simulation results are obtained several conditions like noise effects in up-link path are not significant and TWTA nonlinear effect lead to large signal sidelobe spectrum. Increase IBO of TWTA, increase system performance, on the other hand decrease IBO lead to performance degradation. System performance obtained sub-optimum (nonlinear channel, IBO = 0 dB) for roll-off factor 13 = 0.5625 and obtained optimum (linear channel IBO = 6 dB) for roll-off factor [3 = 0.5. In this research, for sub-optimum condition, on frequency 0.75/T$ , LPF frequency response attenuated 6 dB. For optimum condition, on frequency 0.711\'5 , LPF frequency response attenuated 6 dB. Furthermore, satellite channel is modeled as fourth-order butterworth filter using IBO = 0 dB lead to good performance, but this performance under raised cosine channel condition.